Evaluation of glycemic control, quality of life and psychological characteristics in patients with type 1 diabetes mellitus - Yuliya Andreevna Shishkova; Oleg Gennad'evich Motovilin; Elena Viktorovna Surkova; Alexander Yur'evich Mayorov (Сахарный диабет)
Aim. To identify psychological characteristics associated with better glycemic control and higher quality of life (QoL) in patients with type 1 diabetes mellitus (T1DM). Materials and Methods.  The study included 140 T1DM patients (47 males) aged 18 to 28 years. Assessment of the QoL and associated emotional state (ES) was performed by validated localized questionnaires, supplemented with the inventories for evaluation of psychological characteristics. Based on the acquired data we performed a trilateral analysis of glycemic control, QoL and ES, followed by testing of these parameters for correlation with certain psychological characteristics, including disease attitude, mindfulness, self-attitude and self-assessment, coping strategies, autoregulation parameters and the locus of control. Results.  In the studied sample, better glycemic control was associated with higher QoL and more favourable ES. We also identified several psychological characteristics associated with an improvement in all three primary parameters, namely: higher level of mindfulness, internal locus of control and ergopathic attitude. Conclusion.  The diagnostic inventory for QoL and ES evaluation used in the present study may be helpful for psychological testing in patients with T1DM.